First principle approach towards logic design using hydrogen‐doped single‐strand DNA. Issue 1 (29th October 2018) - Roy, Pradipta; Dey, Debarati; De, Debashis
Abstract : Molecular logic gate has been proposed using single‐strand DNA (ssDNA) consisting of basic four nucleobases. In this study, density functional theory and non‐equilibrium Green's function based first principle approach is applied to investigate the electronic transmission characteristics of ssDNA chain. The heavily hydrogen‐doped‐ssDNA (H‐ssDNA) chain is connected with gold electrode to achieve enhanced quantum‐ballistic transmission along 〈1 1 1〉 direction. Logic gates OR, Ex‐OR, NXOR have been implemented using this analytical model of H‐ssDNA device. Enhanced logic properties have been observed for ssDNA after H adsorption due to improved electronic transmission. Dense electron cloud is considered as logic 'high' (1) output in presence of hydrogen molecule and on the contrary sparse cloud indicate logic 'low' (0) in the absence of hydrogen molecule. Device current is significantly increased from 0.2 nA to 2.4 µA (approx.) when ssDNA chain is heavily doped with hydrogen molecule. The current–voltage characteristics confirm the formation of various Boolean logic gate operations.